Anemia Heart Disease Et Causa Ancylostomiasis - Febriawan, Rahmat; Fauza, Mutiara; Istiana, Trismi (Universitas Malahayati, 2025)
ABSTRACT Anemia is a condition where the hemoglobin concentration is <13g/dL in men and <12g/dL in women, affecting almost a third of the total cases in the global population and is a burden and public health problem. The main pathophysiological mechanisms, based on the strongest evidence-based treatment data, are iron deficiency and inflammation. The study conducted was a case report. Data is obtained through history taking, physical examination and supporting examinations. A 57-year-old woman who works with complaints of weakness since 1 month before entering the hospital which felt worse 7 days ago accompanied by fatigue and lethargy, as well as shortness of breath. Denied complaints of fever, nausea and vomiting, bloody/black stools & stools, denied history of taking painkillers. The patient works as a farmer in a cassava plantation and rarely wears footwear while working. Physical examination of normal TTV, anemic conjunctival head-toe (+/+) and widening of the heart border. Hematological investigations: anemia gravis and increased eosinophils, ECG: LVH, x-ray: cardiomegaly, aortic elongation and pulmonary edema, complete stool examination: ancyolostoma duodenale worm eggs were found. The patient's main patient management was a transfusion of PRC 800 cc, 3x1 FE tablet, albendazole tab 400 mg SD. Keywords: Anemia, Ancylostomiasis, Anemia Heart Disease ABSTRAK Anemia merupakan kondisi dimana konsentrasi hemoglobin <13g/dL pada pria dan <12g/dL pada wanita, mempengaruhi hampir sepertiga dari total kasus populasi global dan merupakan beban serta masalah kesehatan masyarakat. Mekanisme patofisiologi utamanya, berdasarkan data pengobatan berbasis bukti terkuat adalah kekurangan zat besi dan peradangan. Studi yang dilakukan adalah laporan kasus. Data diperoleh melalui anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang. Perempuan 57 tahun dengan pekerjaan dengan keluhan lemas sejak 1 bulan sebelum masuk rumah sakit yang dirasa memberat 7 hari yang lalu disertai letih dan lesu, serta sesak nafas. Keluhan demam, mual-muntah, BAB & BAK berdarah/hitam disangkal, riwayat konsumsi obat antinyeri disangkal. Pasien bekerja sebagai petani di kebun singkong dan jarang mengenakan alas kaki sewaktu bekerja. Pemeriksaan fisik TTV normal, head-toe konjungtiva anemis (+/+) dan pelebaran batas jantung. Pemeriksaan penunjang hematologi: anemia gravis dan eosinophil meningkat, EKG: LVH, rontgen: kardiomegali, elongation aorta, dan edema pulmo, pemeriksaan feses lengkap: ditemukan telur cacing ancyolostoma duodenale. Tatalaksana pasien utama pasien berupa transfusi PRC 800 cc, tablet FE 3x1, albendazole tab 400 mg SD. Kata kunci: Anemia, Ancylostomiasis, Anemia Heart Disease